The fate of transcendentalism : secularity, materiality, and human flourishing - Ronda, Bruce A. (University of Georgia Press, 2017)
The Fate of Transcendentalism examines the mid-nineteenth-century flowering of American transcendentalism and shows the movement's influence on several subsequent writers, thinkers, and artists who have drawn inspiration and energy from the creative outpouring it produced. In this wide-ranging study, Bruce A. Ronda offers an account of the movement as an early example of the secular turn in American culture and brings to bear insights from philosopher Charles Taylor and others who have studied the broad cultural phenomenon of secularization. Ronda's account turns on the interplay and tension.